APX001A Protects Immunosuppressed Mice from Rhizopus delemar Infection. (4th October 2017) - Gebremariam, Teclegiorgis; Alkhazraji, Sondus; Alqarihi, Abdullah; Wiederhold, Nathan P; Shaw, Karen Joy; Patterson, Thomas F; Filler, Scott; Ibrahim, Ashraf
Abstract: Background: Mucormycosis is a life-threatening infection with high mortality that occurs predominantly in immunocompromised patients. APX001A is an antifungal agent that targets Gwt1, an early step in the conserved glycosylphosphotidyl inositol (GPI) post-translational modification pathway of surface proteins in eukaryotic cells. Inhibition of inositol acylation by APX001A results in pleiotropic effects such as inhibition of maturation of GPI-anchored proteins necessary for growth and virulence and results in lethality. APX001A has in vitro activity against Mucorales. Here we assessed the in vivo activity of APX001A against Rhizopus delemar (MIC = 0.25 µg/mL). Methods: ICR mice were immunosuppressed with cyclophosphamide (200 mg/kg) and cortisone acetate (500 mg/kg) on days -2, +3, and +8 relative to intratracheal infection with 2.5 x 10 5 cells of R. delemar 99–880. For survival studies, treatment with APX001 (prodrug) at 52, 104, or 156 mg/kg (twice daily, po), was compared with liposomal amphotericin B (LAmB) at 15 mg/kg (once daily, iv). Treatment started on day +1 through day +8 for APX001 and through day +4 for LAmB. Placebo mice received vehicle control. For fungal burden studies, dosing started 8 hours post infection through day +3. Mice were sacrificed on day +4. Survival time, and tissue fungal burden (by qPCR) served as efficacy endpoints. Results: APX001 treatment at either 52 or 104 mg/kg prolonged survival of mice vs. placebo ( n = 20 per arm) (21-day survival of 0% for placebo, 30% for 52 mg/kg, 45% for 104 mg/kg, P < 0.05 by Log Rank test). APX001 at 104 mg/kg was as good as LAmB treatment (21-day survival of LAmB-treated mice [ n = 20] =50%). APX001 at 156 mg/kg did not enhance survival vs. placebo. Further, APX001 at 104 mg/kg and LAmB reduced pulmonary and brain fungal burden by 1 log and 1.5 log vs. placebo, respectively ( P < 0.05, by Wilcoxon rank-sum). The 52 and the 156 mg/kg APX001 doses also reduced tissue fungal burden vs. placebo mice (0.5–1.0 log). Conclusion: APX001 protected immunosuppressed mice from R. delemar infection with efficacy similar to that of LAmB. Higher doses of APX001 were not protective despite lowering fungal burden. Continued investigation of APX001 as a novel antifungal agent against mucormycosis is warranted. Disclosures: K. J. Shaw, Amplyx Pharmaceuticals Inc.: Employee, Salary; Linnaeus: Consultant, Consulting fee